Effect of application frequency of naphthalene acetic acid on physiomorphological characters and yield of brinjal (Research in Agriculture Livestock and Fisheries, 2018)
A field experiment on brinjal (Solanum melongena cv of brinjal) was conducted at the research field of Regional Horticulture Research Station, Shibpur, Narsingdi during the rabi season of 2016-2017 to find out the suitable application frequency of Napthalene acetic acid (NAA) for higher and profitable yield of brinjal. Napthalene acetic acid (NAA) 40 ppm were sprayed at the different days interval after transplanting (DAT) and flowering initial stage (FIS) of brinjal. Distilled water spray (control) (T0) and five treatments of NAA applications were spraying at 15 DAT (T1), spraying at 15 DAT and at 1st FIS (T2), spraying at 15 DAT then thrice spray at 15 days interval starting from 1st FIS (T3), one spray before 7 days of first flower initiation and thrice spray at 7 days interval starting from1st flower initiation stage (T4) and one spray before 15 days of first flower initiation and thrice spray at 15 days interval starting from 1st flower initiation stage (T5). The NAA application frequencies had no significant effect on plant height, number of leaves/plant, leaf area/plant and specific leaf weight. The T2 and T4 treatments showed identical performances in respect of all parameters and T2 treatment gave maximum total dry matter/plant, long and medium styled flower percent, fruit set percent, number of fruits/plan and fruit yield per hectare.Res. Agric., Livest. Fish.5(2): 151-155, August 2018